Análise crítica do Projeto Político/Ideológico do Movimento Escola Sem Partido - Mierjam, Paulo Augusto (2021)
Currently, society is in a heated debate about the Movimento Escola sem Partido (MESP) that brings to light its impact in the educational and social scope given the nature of its objectives and that can generate a worrying annulment of the rights of teachers and students. Therefore, this research aims to research the MESP, its strategy and its effects in view of the analysis of its main categories. The work was directed to the investigation of the movement within the Gramscian categories of counter-reform and hegemony, in order to understand its proposals as part of a conservative hegemonic strategy, relating it to the historicity of its ideas, linked to a historically privatist and conservative thought crystallized, which seeks to convince society of its point of view, aiming to become common sense. The problem here is to link the movement to the categories in order to unveil its intention, to understand its movement and its contradictions as well as to estimate its impact in the academic and educational scope and in view of this comes our general objective, from which we analyze the Movimento Escola sem Partido (MESP). Specifically, we aim to study the historicity of MESP's ideas in the context of public vs. private disputes in Brazil, listing its proposals for school education, taking as a parameter the social function of the school in modern times, considering the downgrading of the modern school proposal as an element counter-reform and relating the guidelines of MESP with the conservative rise in politics from 2013. At the end we propose through our analyzes to have categorized MESP, unveiling it and in the light of the categories to identify its intentions and its impact in relation to teaching activity and the setbacks that will occur from its implementation.